Sustainable Flame Retardant Coatings Derived from Chinese Lacquer Blend with Synergistic Flame Retardant Silicon-Modified Ammonium Polyphosphate - Shuyun Li; Renjin Gao; Hanyu Xue; Yuchi Zhang; Yuansong Ye; Qi Lin; Qingyou Zeng; Linshishui Liu; Changlin Cao; Jianrong Xia (Advances in Materials Science and Engineering)
The intumescent flame retardant has a high efficiency of carbonization, oxygen barrier, and thermal interruption effect, which is considered to be a promising green and environmentally friendly flame retardant. Herein, we demonstrated a new approach to improve the flame retardant performance of Chinese lacquer films by adding silicon modified ammonium polyphosphate (SAPP), leading to superior flame retardant. SAPP drastically raised the limiting oxygen index (LOI) from 20.1% to 30.6%, and at the same time, the impact resistance was increased from 7 cm to 20 cm without changing the hardness of the lacquer films. X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy were used to investigate the chemical components and morphology of the residual char of Chinese lacquer and SAPP composite films. The thermal degradation process of films was detected and analyzed by thermogravimetry and microcalorimetry, and the possible flame retardant mechanism was discussed. This simple approach opens up a new way to design for improved flame retardancy of organic film polymers.